NILAI ETIKA ISLAMI DALAM KISAH ANAK MUSLIM KARYA KIDH HIDAYAT - Mardiah, Mardiah (BAHASANTODEA, 2017)
The research issue was how the value type, value contents, and the function of islamic ethic value on the story of Moslem Child on Kidh Hidayat Work. This was a qualitative research with descriptive approach. The research data were 38 subtitles in fable called Moslem Child on Kidh Hidayat Work Meanwhile, the data sources were Old Malay prose literature work about the story and supporting theory as the analysis instruments to figure out the research objective. The data collections were done by reviewing documents through the recording and text analysis technique that producing finding. The whole data collected were reviewed by employing qualitative descriptive analysis technique. The analysis results showed that value type, value contents, and the function of ethic value accounted for 303 of ethic values roled by the story actor in the story. Whereas the post analysis results revealed that islamic ethic value type, islamic ethic value contents, and the function of islamic ethic value described that islamic ethic value concerning Almighty God (particularly of Allah SWT; obedience ethic value to Allah SWT, steadyness of faith and faith perfecteness accounted for 175 of islamic ethic value roled by the stroy actor in the story of Moslem Child on Kidh Hidayat Work. The philosophy of islamic ethic value contained in Moslem Child on Kidh Hidayat Work naturally describing Islami way. Therefore, this story can be stated as one of literature learning media on Old Malay prose to guide the characters of the learners on Pancasila characters.